Enacting (real) fiction: Materializing childhoods in a theme park. (May 2015) - Lindgren, Anne-Li; Sparrman, Anna; Samuelsson, Tobias; Cardell, David
Even though fiction and fantasy are fundamental to how childhoods today are understood, this is a topic that is seldom explored either theoretically or academically. We address the question of how the relationship between material real and fictive real can be understood in new ways in contemporary society. We suggest that fiction can be understood in other ways than the hitherto dichotomized approaches to it, and our aim is to focus on the hybridity that is created through the interconnecting word and, as in fiction and childhood and material real and fictive real. This article explores how fiction can be understood as hybrid and interrelated rather than a pure and separate phenomenon, and in particular how materiality as something real and fiction as real mingle. This article introduces ways to talk about the fictive real as realunreality and highlights the drawbacks that might stem from these concepts since in several ways they re-enact childhood innocence and nostalgia, as well as negative differences between childhood and adulthood, where different childhoods share a subordinate position in society.